STANDARDS OPERATING PROCEDURES (SOPS) AS A STRUCTURAL PILLAR OF CARE QUALITY, PATIENT SAFETY, AND ETHICAL TRAINING (CIPEEX, 2025)
Patient safety and quality of healthcare depend largely on the standardization of clinical practices and the systematization of professional conduct. In this context, Standard Operating Procedures (SOPs) emerge as essential tools for standardizing work processes in healthcare and teaching units, ensuring the safe, effective, and uniform execution of healthcare activities. This study consists of a qualitative documentary analysis, focused on the critical synthesis of national and international scientific articles that address the development, implementation, and impact of SOPs in various care settings, with an emphasis on teaching clinics and primary and specialized care units. The objective was to demonstrate, based on the literature, that SOPs are indispensable strategies for patient safety, service efficiency, and the technical and ethical training of health professionals. The methodology involved the systematic reading of studies and their categorization according to thematic adherence, main results, and conclusions. The data revealed that the adoption of SOPs promotes significant improvements in the organization of care processes. In addition, there is a reduction in technical variability, strengthening of autonomy, increased patient safety, and promotion of multidisciplinary team engagement. Furthermore, benefits were highlighted in time management, infection control, implementation of evidence-based practices, and improvement in the quality of practical teaching in academic settings. However, it was observed that the effectiveness of SOPs is directly associated with factors such as institutional support, ongoing training, a favorable organizational culture, and clear communication of protocols. Barriers such as resistance to change, technical ignorance, and lack of infrastructure were also identified as recurring challenges. It can be concluded that Standard Operating Procedures (SOPs) transcend the simple formalization of routines, constituting structural pillars of safe and qualified care. Their implementation should be seen as a strategic action in management, health education, and clinical governance, especially in educational contexts such as university clinics. The integration of theory and practice, promoted by the presence of SOPs in health services, represents an effective pedagogical tool for consolidating clinical and ethical skills, reducing risks, and ensuring patient-centered care. Therefore, investing resources in the development, implementation, and periodic monitoring of SOPs is essential for improving health systems and affirming professional practices in accordance with current technical, scientific, and humanitarian guidelines.
Keywords: standard operating procedures; patient safety; nursing